1984
DOI: 10.2337/diacare.7.6.557
|View full text |Cite
|
Sign up to set email alerts
|

A Four-year Prospective Trial of Unmeasured Diet In Lean Diabetic Adults

Abstract: Fifty-one adult male outpatients at or below ideal body weight (IBW) with no history of weighing more than 15% over IBW in the past 5 yr and no more than 25% in the past 15 yr were randomly assigned to a traditional calorically defined exchange-type diet (EXCH) or an unmeasured diet emphasizing avoidance of refined sugar and balance of food consumption throughout the day. All but 4 patients were insulin treated. With the exception of one patient in each group, all patients were classified as having type II dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…The difference that was observed to be statistically significant among the three strategies was with respect to perceived complexity, indicating that the strategy that utilized carbohydrate counting as a dietary approach (QUANT) was perceived as being more complex compared with the strategies that used the exchange system as a dietary approach (SIMP and QUAL). This finding is contrary to that of other studies that define the exchange system as ‘complex’[15,16,17] and carbohydrate counting as ‘simplified’[15,17,18]. These studies, however, did not assess stress levels or perceptions of complexity.…”
Section: Discussioncontrasting
confidence: 91%
“…The difference that was observed to be statistically significant among the three strategies was with respect to perceived complexity, indicating that the strategy that utilized carbohydrate counting as a dietary approach (QUANT) was perceived as being more complex compared with the strategies that used the exchange system as a dietary approach (SIMP and QUAL). This finding is contrary to that of other studies that define the exchange system as ‘complex’[15,16,17] and carbohydrate counting as ‘simplified’[15,17,18]. These studies, however, did not assess stress levels or perceptions of complexity.…”
Section: Discussioncontrasting
confidence: 91%
“…It is believed [3,13] that a diet low in fat will reduce the incidence of atìierosclerosis in this predisposed population; hence a prevents outpatient diabetics from increasing their total carbohydrate content and decreasing the fat content of their diet [14][15][16]. This is probably due to the ubiquitous presence of sucrose in the usual diet [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of other workers. Gallagher et al (1984) carried out a randomized single blind study over 4 years and found that an unmeasured diet for lean insulin treated Type I1 diabetics is comparable to that of an exchange type, energetically defined, diet in its effect on fasting blood glucose, serum triglyceride, cholesterol and weight. Chandler et al (1983) compared a traditional diet (exchange and pre-planned meals) and a non-traditional diet (a personal guideline system).…”
Section: Discussionmentioning
confidence: 99%